I Identifikasi Kadar Hidrokunon Pada Krim Pemutih Yang Beredar Di Marketplace - Nasiroh, Nasiroh; Rahmadani, Rahmadani; Salwati, Salwati; Alawiyah, Tuti (Jurnal Pelayanan Kefarmasian dan Sains, 2024)
Background: The use of cosmetic products, especially facial whitening creams that contain hydroquinone, can pose a risk to the health of people who use them because they can cause cancer (carcinogenic) and skin disorders such as ochronosis (black skin color). However, in cases in the field, it is often found that hydroquinone content is still present in cosmetic preparations in circulation. Therefore, it is necessary to carry out further research regarding the hydroquinone content in cosmetic preparations. Objective: To determine the content and levels of hydroquinone in samples of whitening cream preparations. Methods: This research uses analytical observational type. Testing was carried out using High Performance Liquid Chromatography (HPLC). Qualitative analysis is carried out by paying attention to retention time, while quantitative analysis is carried out by looking at the area or concentration which is then calculated to obtain hydroquinone levels. Results: The results of research on facial whitening cream circulating in the Shopee, Tokopedia and Bukalapak marketplaces contained hydroquinone in three samples with levels in sample 1 of 0.002204%, sample 4 of 0.03%, and sample 5 of 0.137%.